High levels of used syringe use and unsafe sex among people who inject drugs in Kumasi, Ghana: an urgent call for a comprehensive harm reduction approach - Lisa J. Messersmith; Rose Adjei; Jennifer Beard; Angela R. Bazzi; Joel J. Earlywine; Edwin Darko; Thomas Agyarko-Poku; Mabel Kissiwah Asafo; Sherry Adoma Bempah; Yaw Adu-Sarkodie (BMC, 2021)
Abstract Background Drug use is a growing concern in Ghana. People who inject drugs (PWID) are highly vulnerable to HIV and other infectious diseases. Ghana's National Strategic Plan for HIV/AIDS 2016-2020 identifies PWID as a key population, but efforts to address the needs of PWID have lagged behind those targeting sex workers and men who have sex with men. Lack of information about PWID is a critical barrier to implementing effective HIV prevention and treatment. We aimed to learn more about the vulnerability of the PWID population in order to inform much-needed harm reduction interventions. Methods From April to July 2018, we conducted a mixed methods study in Kumasi, Ghana, to identify all major drug using locations, count the numbers of PWID to obtain rough population size estimations, and administer anonymous surveys to 221 PWID regarding drug use and sexual behavior. We also tested for HIV, HCV, and HBV from syringes used by survey participants. Results Key informants identified five major drug using locations and estimated the total PWID population size to be between 600 and 2000. Enumerators counted between 35 and 61 individuals present at each of the five bases. Sharing syringes and reusing discarded syringes are common practices. Over half of survey participants (59%) reported past-month syringe sharing (34% used a used syringe and 52% gave away a used syringe). Individuals with higher injection frequency (≥ 21 times weekly) and who injected with four or more people had higher odds of syringe sharing. Of the survey participants reporting sex in the last month (23%), most reported having one partner, but only 12% used condoms. Nearly all women (11/13) reported exchanging sex for drugs and 6/13 reported exchanging sex for money in the last six months. Fifteen percent of participants (all men) reported paying for sex using drugs or money. Of the used syringes, prevalence estimates were 3% (HIV), 2% (HCV), and 9% (HBV). Conclusions Our findings confirm the urgent need to implement harm reduction interventions targeting PWID and to build a strong and enabling legal and policy environment in Ghana to support these efforts.